2018
DOI: 10.1111/cas.13569
|View full text |Cite
|
Sign up to set email alerts
|

Established gastric cancer cell lines transplantable into C57BL/6 mice show fibroblast growth factor receptor 4 promotion of tumor growth

Abstract: Previously no mouse gastric cancer cell lines have been available for transplantation into C57BL/6 mice. However, a gastric cancer model in immunocompetent mice would be useful for analyzing putative therapies. N‐Methyl‐N‐nitrosourea (MNU) was given in drinking water to C57BL/6 mice and p53 heterozygous knockout mice. Only 1 tumor from a p53 knockout mouse could be cultured and the cells s.c. transplanted into a C57BL/6 mouse. We cultured this s.c. tumor, and subcloned it. mRNA expression in the most aggressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

7
1

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 18 publications
0
40
0
Order By: Relevance
“…We have previously reported that tumor growth, metastatic rate and peritoneal dissemination rate of YTN16 were higher than YTN2; FGFR4 expression by YTN16 cells was 121-fold higher than YTN2. 8 We demonstrated that FGFR4 disruption by CRISPER-Cas9 system or pharmacological inhibition of FGFR signaling in YTN16 resulted in the reduction of peritoneal dissemination. In this study, we focused on the immunological aspects of these two tumor cell lines.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…We have previously reported that tumor growth, metastatic rate and peritoneal dissemination rate of YTN16 were higher than YTN2; FGFR4 expression by YTN16 cells was 121-fold higher than YTN2. 8 We demonstrated that FGFR4 disruption by CRISPER-Cas9 system or pharmacological inhibition of FGFR signaling in YTN16 resulted in the reduction of peritoneal dissemination. In this study, we focused on the immunological aspects of these two tumor cell lines.…”
Section: Discussionmentioning
confidence: 83%
“…YTN2 and YTN16 gastric cancer cell lines are subclones of one line established from a tumor induced by N-methyl-N-nitrosourea treatment of a male heterozygous p53 knockout mouse. 8 YTN2 spontaneously regresses in C57BL/6 mice in a CD8 + T cell-dependent manner, while YTN16 grows progressively ( figure 1 ). These two related cell lines both harbor a similar number of mutation-associated neoantigens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…YTN16 cells were established from subcutaneous tumors by injection of primary cultured cells derived from a mouse gastric adenocarcinoma. Mouse gastric tumors were established in p53 heterozygous knockout C56BL/6 mice by addition of N-Methyl-N-nitrosourea (MNU) to the animals' drinking water [23]. The resulting tumor cells were cultured in high-glucose Dulbecco's modi ed Eagle medium (DMEM, Sigma-Aldrich Japan, Tokyo, Japan) containing 1.0mL/L MITO (Coning Japan, Tokyo), 10mL/L L-Glutamine, 10mL/L Penicillin/Streptomycin and 10% fetal bovine serum (FBS), on plastic dishes coated with Type I collagen solution (0.5% Atelocollagen Acidic Solution IPC-50; Koken Co., Ltd., Japan) at 37°C in 5% CO 2 atmosphere.…”
Section: Cell Lines and Cell Culturementioning
confidence: 99%
“…BLU9931 makes a covalent bond with Cys552 within the ATP-binding pocket of FGFR4, which is not present in FGFR1-3. BLU9931 inhibited gastric cancer cell growth in a transplanted mouse model [ 36 ]. To date, however, there have been no reports about the effects of FGFR4 inhibitors in PDAC.…”
Section: Introductionmentioning
confidence: 99%